Primary multi-systemic metastases in osteosarcoma: presentation, treatment, and survival of 83 patients of the cooperative osteosarcoma study group - Mettmann, Vanessa; Blattmann, Claudia; Friedel, Godehard; Harrabi, Semi B.; Kalle, Thekla von; Kager, Leo; Kevric, Matthias; Kühne, Thomas; Nathrath, Michaela; Sorg, Benjamin; Werner, Mathias; Bielack, Stefan S.; et al. (Cancers, 2024)
BACKGROUND: To evaluate patient and tumour characteristics, treatment, and their impact on survival in patients with multi-systemic metastases at initial diagnosis of high-grade osteosarcoma. Precedure: Eighty-three consecutive patients who presented with multi-systemic metastases at initial diagnosis of high-grade osteosarcoma were retrospectively reviewed. In cases of curative intent, the Cooperative Osteosarcoma Study Group recommended surgical removal of all detectable metastases in addition to complete resection of the primary tumour and chemotherapy. - RESULTS: Eighty-three eligible patients (1.8%) were identified among a total of 4605 individuals with high-grade osteosarcoma. Nine (10.8%) of these achieved complete surgical remission, of whom seven later had recurrences. The median follow-up time was 12 (range, 1-165) months for all patients. Actuarial event-free survival after 1, 2, and 5 years was 9.6 ± 3.2%, 1.4 ± 1.4%, and 1.4 ± 1.4%, and overall survival was 54.0 ± 5.6%, 23.2 ± 4.9%, and 8.7 ± 3.3%. In univariate analyses, elevated alkaline phosphatase before chemotherapy, pleural effusion, distant bones as metastatic sites, and more than one bone metastasis were negative prognostic factors. Among treatment-related factors, the microscopically complete resection of the primary tumour, a good response to first-line chemotherapy, the macroscopically complete resection of all affected tumour sites, and local treatment (surgery ± radiotherapy) of all bone metastases were associated with better outcomes. Tumour progression under first-line treatment significantly correlated with shorter survival times. - CONCLUSION: The outlook for patients with multi-systemic primary metastases from osteosarcoma remains very poor. The utmost importance of surgical resection of all tumour sites was confirmed. For unresectable bone metastases, radiotherapy might be considered. In the patient group studied, standard chemotherapy was often insufficiently effective. In the case of such advanced disease, alternative treatment options are urgently required.